Three key success factors for transforming your business mindset, infrastructure, capability - Hagemann, Michael (Human resource management and organizational behavior collection, 2020)
Chapter 1. Introduction -- Chapter 2. Change management in the 21st century -- Chapter 3. Mindset -- Chapter 4. Infrastructure -- Chapter 5. Capability -- Chapter 6. How MIC is applied